2020
DOI: 10.1111/jocs.14460
|View full text |Cite
|
Sign up to set email alerts
|

Causes and characteristics associated with early and late readmission after open‐heart valve surgery

Abstract: Objectives The objectives of the study were to describe the causes of readmission from discharge to 30 days and from day 31 to 180 after discharge and to investigate the characteristics associated with overall and cause‐specific readmissions after open‐heart valve surgery. Methods A single‐center, retrospective cohort of 980 patients undergoing open‐heart valve surgery from 2013 to 2016. Time to the first readmission was analyzed using univariable and multivariable Cox proportional hazard models. Results are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 28 publications
3
10
1
Order By: Relevance
“…The incidence of significant pericardial effusion (16%) found in the current study is seemingly high when compared with previous studies 1 4–9. This can be explained by several factors: several studies report incidences of significant pericardial effusions based on broad cardiac surgical populations, including patients undergoing isolated CABG.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…The incidence of significant pericardial effusion (16%) found in the current study is seemingly high when compared with previous studies 1 4–9. This can be explained by several factors: several studies report incidences of significant pericardial effusions based on broad cardiac surgical populations, including patients undergoing isolated CABG.…”
Section: Discussioncontrasting
confidence: 68%
“…Thus, it is expected that our study, only including patients undergoing valve surgery, will find a higher proportion of pericardial effusions. In addition, the definition of significant pericardial effusion versus cardiac tamponade varies across studies1 4–9 18 and in the current study, all significant pericardial effusions requiring drainage were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients admitted for open-heart surgery, the readmission rate in our study was 16.3%. Similarly, a retrospective study gathered in New York, United States, showed the readmission rate was 16.5% (12) . On the other hand, a separate study in Florida, United States, was 23% (16) .…”
Section: Discussionmentioning
confidence: 93%
“…Lowering hospital readmission rates has been considered an effective method to enhance the quality of care and reduce costs (11) . Nevertheless, a retrospective cohort study in the United States between January 1, 2005, and November 30, 2007, showed that the 30-day readmission rate after cardiac surgery ranged from 8.3% to 21.1%, with the most common reasons for readmission being postoperative infection (16.9%) and heart failure (12.8%) (12) . Iribarne and colleagues in a prospective study reported that the overall rate of readmission was 18.7% with female gender, diabetes mellitus, COPD, elevated creatinine, and lower hemoglobin being the top most common risk factors for re-admission after cardiac surgery (13) .…”
Section: Discussionmentioning
confidence: 99%